LAW ENFORCEMENT ON CORRUPTION CASES IN VIETNAM - Phạm Thanh Mai (DUTA BANGSA UNIVERSITY INDONESIA, 2020)
This research examines corruption offences in public investment in Vietnam. An important part of the research is to examine and evaluate effectiveness and accountabilities of anti-corruption in public investment in Vietnam, including the Government Inspectorate of Vietnam, the People’s Procuracy of Vietnam and the People’s Public Security Forces of Vietnam based on their functions, powers and responsibilities. The aim of this research was to examine corruption and criminal behaviour in public investment in Vietnam, to identify practical policies, models and strategies for the purpose of improving the capacities and effectiveness of anti-corruption in public investment in Vietnam. The overall objective of this research was to research the corruption offences in public investment in Vietnam; to evaluate the effectiveness and accountabilities of anticorruption in public investment in Vietnam, including the Government Inspectorate of Vietnam, the People’s Procuracy of Vietnam and the People’s Public Security Forces of Vietnam based on their functions, powers and responsibilities; and to analyse corruption offences in public investment in terms of organisational structures and criminal behaviour to identify practical recommendations to enhance the success in combating corruption in public investment in Vietnam. A combination of qualitative and quantitative methods was employed in this study. The research has implications for anti-corruption commission policy makers and researchers in Vietnam.